Security Analysis Using Blockchain Based Key Aggregation Cryptosystem with Time Complexity Reduction - Nanda, Ipseeta; Khatua, Lizina; N. Rajendran; Marandi, Arun Kumar; Manjunath CR; Sathish M. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
One of the rapidly developing technologies that is important in field of criminal investigation is blockchain. In recent years, security has grown to be a serious danger to every industry, including banking, supply chain management, smart applications, and IoT. In this research proposed method has to increase the public auditing performance using blockchain based key aggregation cryptosystem (BKAC) in cloud computing. Proposed system is found to be very efficient for sharing the data then it is able to avoid and provide more security by using blockchain based key aggregate cryptosystem with the help of wallet generator. Finally, the suggested system is subjected to performance and security research to ensure that it is well suited for cloud data sharing. Time complexity must be reduced. The parameteric analysis has been carried out in terms of Completion Ratio, Throughput, Degree of Imbalance, Scalability, QoS. . the proposed technique attained Completion Ratio of 61%, Throughput of 92%, Degree of Imbalance of 66%, Scalability of 67%, QoS of 62%.